Do berimbau à caneta : a mandinga literária em Machado de Assis, Conceição Evaristo, Allan da Rosa e Cidinha da Silva - Oliveira, Katiane Martins de (2024)
The term "literaginga" is epistemic as it situates "literature" and "ginga" (swing) as producers of critical power and subjectiveness. This term also raises questions about literary production and establishes a methodology conceived from creating a reading device for literature analysis. The concept of literaginga acts as an instance of movement, allowing a changing perspective on the aesthetics and writing ideas presented throughout this work. This dissertation displays a synesthetic resource, bringing strong elements from Afro-Brazilian cultural memory, such as capoeira, for its symbolic content, to engage with tools used in literature. Four short stories were analyzed to verify the category "Teoria do Medalhão" by Machado de Assis, "Chão" by Allan da Rosa, "Os amores de Kimbá" by Conceição Evaristo, "Jangada é pau que boia" by Cidinha da Silva. Furthermore, it was possible to present and apply four characteristics that support this analytical category and its functionality, testifying and legitimizing literaginga as a term which are: 1. Semantic configuration in orality; 2. Oralized, embodied, and aesthetic movements present in literature (Afro Brazilian); 3. Mandinga: problematization in a non-direct manner; 4. Cadence: verbal rhythm. For this purpose, the theoretical framework was used considering literature aspects, referencing Antônio Candido (2006) to understand the relationship between literature and society. To expand discussions about Afro-Brazilian literature, Cuti (2010). The field of performance studies was consulted to connect with literature studies. Additionally, the philosophy and knowledge from capoeira masters were invoked to reflect on their cultural and social importance. The objective aimed to verify the applicability of the literaginga`s concept to construct a dialectic connection among capoeira and literature, understanding the development and deepening of new knowledge methodologies